2021
DOI: 10.1109/access.2021.3098172
|View full text |Cite
|
Sign up to set email alerts
|

Design of a New Tukey MA-DEWMA Control Chart to Monitor Process and its Applications

Abstract: Control chart is a useful statistical tool for the production process control to maintain the product value at the standard. The objectives of this research were to propose the Tukey Moving Average -Double Exponentially Weighted Moving Average control chart (MMD-TCC chart) to detect the change of mean in the symmetric and non-symmetric distribution, and to compare the effectiveness of the change detection of MMD-TCC with that of MA, DEWMA, MMD, MDM, TCC, and MDM-TCC at the different parameter levels. ARL 1 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…where the sample size is set to 𝑁 = 𝟏 𝑇 𝒂 𝑙𝑘,𝑡 (𝑔) = 1 . As Taboran et al [30] pointed out, a monitoring statistic becomes more sensitive to small and moderate magnitude of process shifts when current and past samples are combined with a framework of exponentially weighted moving average (EWMA). Assume the smoothing parameter 0 < 𝜆 < 1, the combined observations will be…”
Section: Proposed Control Chartmentioning
confidence: 99%
“…where the sample size is set to 𝑁 = 𝟏 𝑇 𝒂 𝑙𝑘,𝑡 (𝑔) = 1 . As Taboran et al [30] pointed out, a monitoring statistic becomes more sensitive to small and moderate magnitude of process shifts when current and past samples are combined with a framework of exponentially weighted moving average (EWMA). Assume the smoothing parameter 0 < 𝜆 < 1, the combined observations will be…”
Section: Proposed Control Chartmentioning
confidence: 99%
“…For example, Abbas et al [1] use the exponentially weighted moving average (EWMA) statistic as the input into a cumulative sum (CUSUM) chart in their approach. Similarly, the approach of Taboran et al [2] uses a moving average (MA) as the input into a double EWMA chart. Knoth et al [3] have shown that the justification of some of these ad hoc methods is inadequate.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the approach of Taboran et al. [2] uses a moving average (MA) as the input into a double EWMA chart. Knoth et al.…”
Section: Introductionmentioning
confidence: 99%
“…Riaz et al [ 25 ] designed mixed Tukey EWMA-CUSUM chart (MEC-TCC). Taboran et al [ 26 , 27 ] investigated a Tukey MA-EWMA control chart and a Tukey MA-DEWMA control chart for the monitor mean process, respectively. Khaliq et al [ 28 ] suggested a median-based design for Tukey and Tukey-EWMA control charts under subgrouping, and etc.…”
Section: Introductionmentioning
confidence: 99%